2014
DOI: 10.1063/1.4873297
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable and non-volatile vertical magnetic logic gates

Abstract: In this paper, we discuss the concept and prototype fabrication of reconfigurable and non-volatile vertical magnetic logic gates. These gates consist of two input layers and a RESET layer. The RESET layer allows the structure to be used as either an AND or an OR gate, depending on its magnetization state. To prove this concept, the gates were fabricated using a multi-layered patterned magnetic media, in which three magnetic layers are stacked and exchange-decoupled via non-magnetic interlayers. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…11 We found that the SW frequency dependence on the applied magnetic field can be well reproduced by a theoretical model based on the thin film formalism and including the effect of the AFM/FM exchange coupling.…”
mentioning
confidence: 90%
“…11 We found that the SW frequency dependence on the applied magnetic field can be well reproduced by a theoretical model based on the thin film formalism and including the effect of the AFM/FM exchange coupling.…”
mentioning
confidence: 90%
“…Moreover, they offer possibilities for reconfigurable magnonic crystals that display reprogrammable band structure [7,8]. In order to optimize and tailor their technological applications [9,10], it is essential to gain a fundamental understanding of the magnetization dynamics in these structures. In general the properties can be quite complex, because of the interplay between shape anisotropy (in both the lateral and depth dimensions of the NWs), other boundary anisotropies in the NWs, asymmetries due to different variations in the geometric arrangement of NWs, and the competing effects of shortrange exchange and long-range dipole-dipole interactions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to remark that one specific advantage of the proposed layered structure over planar systems, is that by using a single fabrication mask one can fabricate multilayered structure with different thicknesses of the layers and thus multiple reprogrammable magnetization configurations and dynamic responses. In this respect, layered structures are also interesting as prototypes of multiple magnetic storage layers 32 and as non-volatile vertical magnetic logic gates 33 where the knowledge of the SW properties is important because they represent a source of noise in reading heads 34 as well as a source of energy consumption during the magnetization reversal process 35 . In addition, exploring the third dimension in magnonics is important in order to follow the latest trend in CMOS electronics where expansion from two-dimensional planar to three-dimensional vertically integrated structures is now pursued 36,37 .…”
Section: Introductionmentioning
confidence: 99%